Halogenated Secondary Metabolites from Sea Hare Aplysia dactylomela - C.S, Vairappan,; K.L, Tan, (Malaysian Journal of Science, 2005)
Sea hare, Aplysia dactylomela, from North Borneo waters was investigated for its secondary metabolite content. Investigation resulted in the isolation and identification of three halogenated sesquiterpenes; Palisadin A (1), Aplysistatin (2) and 5-acetoxypalisadin B (3). Compounds were present in significant quantity, 5 %, 3 % and 3 % of crude extract, respectively. The same compounds were also isolated from Laurencia snackeyi found growing in the same location where the sea hare was collected. Further bioassay experiments showed interesting pattern in their antimicrobial activities; Palisadin A (1) showing > 83% inhibition against tested organisms and Aplysistatin (2) exhibited > 27% activity. However, 5-acetoxypalisadin B (3) did not show any inhibition against the tested organisms.